Urban Anti-Eviction Social Movement - Hidayat, Miftahul; Sari, Ramadhanita Mustika (Journal of Contemporary Sociological Issues, 2024)
This research aims to explain the phenomenon of the Anti-Eviction Movement in Makassar as a case that represents the formation of civil society in East Indonesian city. Using the case study method, this research focuses on aspects related to the struggle for the right to the city and the right to a safe place to live from the threat of eviction based on primary and secondary data. The primary data comes from interviews with participants of the bara-barayya alliance movement in Makassar City conducted from January 2023 to July 2023. In the interviews, the researcher concentrated on how the bara-barayya alliance movement expressed their struggle to claim the right to the city and a safe home from the threat of eviction. Data analysis was conducted through interview analysis to obtain accurate data and describe and explain the data explicitly. The findings in this study show that the feeling of threat among urban residents who face the threat of eviction creates resistance through the anti-eviction movement to claim their right to shelter and housing and the struggle to reclaim their right to the city. This study argues the crucial and urgent importance of understanding urban anti-eviction social movements in various cities to prevent evictions in Indonesia. Mainly to construct the effectiveness of social activism. Keywords: Activism, Anti-Eviction, Urban Social Movement, Makassar, Indonesia